2022
DOI: 10.1371/journal.pone.0264836
|View full text |Cite
|
Sign up to set email alerts
|

Promoting mechanism of serum amyloid a family expression in mouse intestinal epithelial cells

Abstract: Serum amyloid A (SAA) is an acute phase inflammatory protein that we previously described as a robust biomarker of colorectal inflammation in patients with ulcerative colitis (UC) in clinical remission. However, what induces SAA expression in UC remains unclear. This study demonstrates that SAA is significantly expressed in the intestinal tract of UC mouse models when compared with C-reactive protein, another inflammatory biomarker. Moreover, interleukin-6 and tumor necrosis factor-α were found to promote SAA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In humans, SAA1 and SAA2 are considered acute phase reactants, whereas in pigs, the SAA3 isoform is the major acute phase protein induced in response to an inflammatory stimulus ( 56 ), which was also shown in the present study. TNFα is one of the major inducers of SAA synthesis in the liver, and it has also been shown that the production of SAA is increased in intestinal epithelial cells following TNFα stimulation, possibly contributing to the development of inflammatory bowel disease ( 57 , 58 ). In urothelial cells, expression of SAA has been shown to increase upon infection with uropathogenic bacteria E.coli ( 59 ), whereas Lannergard et al.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, SAA1 and SAA2 are considered acute phase reactants, whereas in pigs, the SAA3 isoform is the major acute phase protein induced in response to an inflammatory stimulus ( 56 ), which was also shown in the present study. TNFα is one of the major inducers of SAA synthesis in the liver, and it has also been shown that the production of SAA is increased in intestinal epithelial cells following TNFα stimulation, possibly contributing to the development of inflammatory bowel disease ( 57 , 58 ). In urothelial cells, expression of SAA has been shown to increase upon infection with uropathogenic bacteria E.coli ( 59 ), whereas Lannergard et al.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind this is that SAA3 upregulates IL-22 expression in colon mucosal neutrophils through a TLR2-dependent signal pathway, which can restrain chronic inflammation [ 63 67 ]. Interestingly, rectal expression of SAA3 is significantly increased by IL-22 [ 68 ].
Fig.
…”
Section: Saa In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…It has been reported that SAA expression could be induced by bacterial-derived products. Specifically, bacterial lipopolysaccharides could promote SAA expression [ 43 , 68 ]. In addition, the segmented filamentous bacteria adhering to mice intestinal epithelial cells could cause an accumulation of TH17 cells in the lamina propria, whose SAA1-3 transcriptions are significantly upregulated [ 82 ].…”
Section: Saa In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…5A). Serum amyloid A (SAA) is a major protein marker of colitis disease activity, 47,48 and promotes intestinal inflammation. 49 Furthermore, we measured the protein level of SAA in the serum to gain further insight into the suppression of colitis by ADNs.…”
Section: Adns Reduce the Expression Of Pro-inflammatory Cytokines And...mentioning
confidence: 99%